RADIATION AND THERMAL HARDNESS OF THIN LAYERS, HETEROSYSTEMS AND NANOSTRUCTURES WHICH PRODUCED ON THE BASIS OF ELEMENTARY SEMICONDUCTORS AND SEMICONDUCTOR COMPOUNDS - Баранський, Петро Іванович; Гайдар, Г. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The particularities of size and structure of nanoobjects leads to set of specific properties. So, the developed surface determines the increased chemical reactivity; the high level of discontinuity results in lack of lattice constant and disturbance translation symmetry; the size of intrinsic variations of potential on distance, which may be commensurable with interatomic distances, prejudices the appropriateness of effective mass method; etc. The presence of huge mechanical stresses and difference of thermal expansion coefficients can stimulates the structure degradation processes under change of temperature conditions. The preventive measures to decrease the rate of degradation processes in the nanostructures will be discussed.